Analisis Kesalahan Umum dalam Tata Persuratan dan Upaya Pencegahannya: Studi Kasus di Yayasan Pendidikan Prima Swarga Bara (YPPSB) - Iswanto; Fitriah Amina; Siti Maryam (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
The Prima Swarga Bara Education Foundation (YPPSB) recognizes the importance of proper and effective writing in ensuring good communication with various parties, including students, parents, staff, and partners. This research uses a qualitative approach with text analysis and interview methods to delve into the complexities of writing errors. This approach is chosen because the main focus of the research lies in identifying and understanding in depth the errors in official letters through careful analysis of letter examples. Analysis of common grammatical errors found, such as the use of incorrect words, ineffective sentences, and misuse of punctuation. In the case of the announcement letter for the results of the YPPSB PPDB 2021-2022, there is an error in the section "Dear Mr./Mrs." (should be "Dear Mr./Mrs. [Recipient Name]". In addition, there is the use of informal language that is not in accordance with the context of an official letter. Grammatical and spelling errors indicate a lack of attention to detail and professionalism on the part of the sender. This can make the recipient doubt the sender's credibility and ability to convey the message. Writing errors, such as grammatical, spelling, format, and structural errors, can have a serious impact on the recipient's perception and the overall effectiveness of communication.